Telephone Calls from The Dead: A Revised Look at the Phenomenon Thirty Years On by Callum E. Cooper - Haraldsson, Erlendur (Journal of Scientific Exploration, 2013)
Telephone Calls from the Dead deals with a topic rarely touched upon since Rogo and Bayless published their classic Phone Calls from the Dead (1979). This book gives a review of how this field has developed, presents a number of old and new cases, and deals at length with various explanations of the phenomenon and its technical aspect. And it is very readable. The book reviews collections of case reports of spontaneous phone calls from the dead, primarily Bayless and Rogo’s 50 cases suggestive of anomalous communication that were collected in the 1960s. They divided the cases into a few categories, such as simple calls where the dead caller says only a few words and is unresponsive to questions, which brings the call to an end. Second, prolonged calls that involve a conversation, and third, answer calls where living persons make a call to someone they do not know has died and yet they get an answer. There are also cases involving disconnected telephones. This fascinating anecdotal material has undergone considerable investigation and scrutiny. During the 1980s, some 40 Italian cases were collected by Massimo Biondi. After interviewing the receivers of the calls and additional witnesses, Biondi concluded that 20 of these cases still appeared to be inexplicable.